Perfil neurocomportamental e reprodutivo de Drosophila melanogaster expostas durante o desenvolvimento ao Bisfenol F e Bisfenol S - Musachio, Elize Aparecida Santos (2024)
Bisphenol A (BPA), present in objects of daily use and food packaging, is attributed to the development of damage to the reproductive and neurological systems. Based on this, the industry began to replace it with other substances with homologous chemical structures. Among several, Bisphenol F (BPF) and Bisphenol S (BPS) are the most applied in consumer products, even though there is a lack of data on the effects of these analogues on the body. Therefore, the objective of this thesis was to investigate the effects of BPS and BPF on the neurobehavioral profile of both sexes and reproductive capacity of Drosophila melanogaster females exposed during the development period. For this, the parental flies were divided into a control group (standard diet), BPS and BPF, both at concentrations of 0.25, 0.5 and 1 mM (added to the diet). After 7 days of exposure, the progenitors were removed, and the treated vials containing the filial generation 1 (F1) were preserved for this research, which is divided into two stages. The 1st stage is related to the toxicological action of BPF and BPS on neurodevelopment, and is subdivided into two parts: evaluation in the larval phase and later in the adult phase (fly). 3rd-stage larvae were used, which showed increased activity of antioxidant enzymes (superoxide dismutase and catalase). An increase in cytochrome P-450 (CYP450) activity was also observed, which may be associated with the possible production of toxic metabolites, culminating in increased reactive species and lipid peroxidation, reducing mitochondrial and cellular viability. These results justify the reduction in the rate of larval pupation and pupal emergence due to oxidative stress induced by BPF and BPS. Complementary to these results, larvae exposed to BPF and BPS showed abnormal behaviors, characteristic in models of neurodevelopmental diseases, such as locomotor hyperactivity associated with reduced reorientation capacity within the test arena, preference for light, reduced sensitivity to heat and cold, and less responsiveness to touch. However, the second phase of evaluation was carried out with flies (F1 after emergence), and it was evidenced that changes in the behavioral profile of Drosophila melanogaster continued until adulthood. As adults, flies exposed to BPF and BPS during development showed atypical behaviors such as hyperactivity, cognitive reduction in the learning test and changes in social interaction capacity. Furthermore, the flies reproduced repetitive grooming behaviors and became more aggressive. This data set may be an effect attributed to reduced Shank protein in flies and increased brain size. The 2nd stage of the work is presented as manuscript 2; however, it is possible to observe that female flies exposed during development to BPF and BPS showed a reprotoxic effect, evidenced by changes in ovarian morphology and a corresponding reduction in fertility. These data may be related to decreased expression of the ecdysone receptor (EcR). BPF and BPS may have acted as endocrine disruptors, binding to EcR, impairing ecdysone production and signaling. In addition to damage to the ovarian structure, this effect altered the flies' physical characteristics such as wing size and body weight. Therefore, this data set refutes the idea that BPF and BPS are safe substances and elucidates that oxidative stress induced by exposure to both substances during the development of Drosophila melanogaster altered the neurobehavioral profile of both sexes and caused reproductive damage in females.